Actualidad y proyecciones de la maternidad subrogada en el derecho internacional privado argentino - Brodsky, Jonathan Matías (2013)
Surrogate motherhood, as well as assisted reproductive technology, are today\na fact which neither civil nor international law can longer ignore. The silence on the matter\nof the current Argentinean law is unacceptable. However, the Civil Code Reform Bill\ntimely addresses surrogate motherhood, both in civil and international spheres.After briefly considering the (in)convenience of the law allowing this kind of practice,\nthis essay will deal with the legal requirements established in the Reform Bill\nfor surrogate motherhood to be admitted ? international public order requirements.\nFurthermore, competent jurisdiction and applicable law criteria on the matter will\nalso be examined, as well as filiation recognition having been born through surrogate\nmotherhood in a foreign country (where its law allows this practice).\nFinally, the essay will address the interaction between international public order and\nthe best interest of the child, and whether and how the Reform Bill could be applicable\ntoday ? given the silence of the law currently in force.